Model Predictive for Phase Current of Three Phase Two Level Inverter Considering the Dead Time and Clamping Effect - Wang, Jianyuan; Xiang, Li; Jia, Lingxian (2018 IEEE International Power Electronics and Application Conference and Exposition (PEAC), 2018)
In the digital regulation of power electronics systems the sampling of system variables plays an important role. Fast and accurate sampling is nowadays a popular research subject. In recent years, many researches are invested to improve the sampling using predictive model. This paper presents an improved predictive model, which can be used to predict the moving average value of the three phase two level inverter phase current accurately, even though the dead time and the zero current clamping effect are existed. This method was validated using simulation and experiments.